Nilai-Nilai Pendidikan Karakter Dalam Kesenian Kompang: (Analisis Kesenian Kompang Di Desa Pasiran, Bengkalis, Riau) - Susanti, Triana; Puji Rusmawati , Dewi; Delfina, Fiffy (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Kompang art is a traditional art that still exists today, and is still widely used in formal events such as plain flour pats. Kompang is an art that already has a lot of customs in it which shows identity as a Malay nation that upholds art with a touch of Islamic law. In this paper the author is interested in discussing the character values contained in the Kompang art in Pasiran Village. Using a qualitative descriptive method, this study conducted in-depth interviews with one of the informants, namely Mr. Kasim who lives in Pasiran Village who is the owner of the Kompang Pasiran art studio. Then do an analysis that this Kompang art has existed for a long time, and has moral and aesthetic values in it. Where Hindu teachings are still felt so strong in the use of the tools used in every plain flour patting event, but the Islamic teachings that have been assimilated into it bring prayers and sholawat in the book of al Barzanji to make the connection with Islamic law so felt. With the existence of Islamic teachings, this will make the character and personality of the local community better in attitude, behavior, in accordance with Islamic teachings contained in the Kompang art